Carbon Nanomaterials‐Enabled High‐Performance Supercapacitors: A Review. Issue 2 (8th December 2022) - Li, Yuanyuan; Zhao, Fu-Gang; Liu, Li-Na; Xu, Zi-Wen; Xie, Guanghui; Li, Jingjing; Gao, Tianzeng; Li, Wenguo; Li, Wei-Shi
Abstract : Supercapacitors (SCs), an important kind of electrochemical energy storage device, are featured with high power density, rapid charging and discharging, and ultralong cycling lifespan and have been widely applied in multiscenario energy storage and output systems, such as portable consumer electronics, electric vehicles, and reservoir setups for green and sustainable energy resources. Among their components, electrode materials are of primary importance in dictating their performances. Owing to good electric conductivity, achievably large specific surface area, low cost, chemical stability, and easy loading with other electrochemically active species, various carbon nanomaterials, including activated carbons, carbon nanotubes, graphene, and other porous carbons, are promising electrode materials in the fabrication of high‐performance SCs. In fact, the past decade has witnessed enormous efforts in the development of high‐performance carbon‐based SC electrode materials and great progresses achieved in the field. In this review, recent advances on these carbon‐based SCs are summarized through a number of selected representative works. In each one, the unique preparation method, structural features, and their correlations to electrochemical properties and final SC performance are presented and discussed. At the end of the review, the challenges and future developing prospects are briefly outlined. Abstract : The article reviews the recent advances of supercapacitors (SCs) made from various carbon nanomaterials, including activated carbons, carbon nanotubes, graphene, and other porous carbons, with the emphases on material preparation methods, structural features, and electrochemical properties and final SC performance.